Identification of Nepal’s Soft Power - Timilsana, Binod Khanda (Saptagandaki Journal, 2021)
Soft power, according to Nye, is a particular power of attraction to a state based on the appeal of its culture, political values, and foreign policies (Nye Jr. 2004, p. 11, 2008, p. 96). In the changing paradigms of state powers from military strength, economic might, political power, technological competency to soft power endeavors, identification of own soft power is the process of measuring own strength. Hard power measures can be observed from out sides as well but soft power potentialities will not appear easily without systematic attempt to expose them in front of international actors. Hard power measurement is easy and more exact than soft power qualities. There are very limited academic attempts visible in identification of Nepal’s soft power. Great soft powers of the world are visible and measurable through soft power indices developed by different think tanks and research agencies. The soft power 30 and Global Soft Power Index are exemplary forums engaged in ranking states in terms of soft powers. Reputation, influence, political values, culture, foreign policies, enterprise, culture, digital, governance, engagements and education are the indicators of soft power. The newly explained taxonomy of soft power includes four subunits of soft power namely resources, instruments, receptions and outcomes. Buddhism is a powerful soft power resource of Nepal. Conflict resolution and peace process model of Nepal is another potential soft power. Culture, engagement in multilateral global and regional forum, natural beauty with the world is highest Mt. Everest, diasporic community of Nepal, social networks, public diplomacy and personal diplomacy are remarkable soft power properties of Nepal. Nonetheless, identification of Nepal’s soft power is in very preliminary phase.